2016
DOI: 10.1038/srep37804
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium MAV2054 protein induces macrophage apoptosis by targeting mitochondria and reduces intracellular bacterial growth

Abstract: Mycobacterium avium complex induces macrophage apoptosis. However, the M. avium components that inhibit or trigger apoptosis and their regulating mechanisms remain unclear. We recently identified the immunodominant MAV2054 protein by fractionating M. avium culture filtrate protein by multistep chromatography; this protein showed strong immuno-reactivity in M. avium complex pulmonary disease and in patients with tuberculosis. Here, we investigated the biological effects of MAV2054 on murine macrophages. Recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 59 publications
(72 reference statements)
4
27
0
Order By: Relevance
“…We observed, inhibiting caspase-12 significantly down-regulated the activation of caspase-9/3 axis, suggesting that caspase-9 can be activated by multiple pathways in M. fortuitum infected HKM. The involvement of caspase-9 is well documented in pathogenesis induced by several mycobacteria 12 , 43 – 45 our study extends this to M. fortuitum .…”
Section: Discussionsupporting
confidence: 80%
“…We observed, inhibiting caspase-12 significantly down-regulated the activation of caspase-9/3 axis, suggesting that caspase-9 can be activated by multiple pathways in M. fortuitum infected HKM. The involvement of caspase-9 is well documented in pathogenesis induced by several mycobacteria 12 , 43 – 45 our study extends this to M. fortuitum .…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have focused on controlling mycobacteria by exploiting host innate immunity, principally apoptosis (Behar et al, ; Bhattacharyya et al, ; Parandhaman & Narayanan, ). In M. avium ‐infected macrophages, reactive oxygen species (ROS) induce caspase‐dependent apoptosis by disrupting the mitochondria membrane potential, precipitating release of cytochrome c (Lee et al, ). Previously, we reported that endoplasmic reticulum (ER) stress‐mediated apoptosis through ROS regulates the intracellular survival of mycobacteria in macrophages (J.…”
Section: Introductionmentioning
confidence: 99%
“…In M. avium-infected macrophages, reactive oxygen species (ROS) induce caspase-dependent apoptosis by disrupting the mitochondria membrane potential, precipitating release of cytochrome c (Lee et al, 2016). Previously, we reported that endoplasmic reticulum (ER) stress-mediated apoptosis through ROS regulates the intracellular survival of mycobacteria in macrophages (J.…”
Section: Introductionmentioning
confidence: 99%
“…Using this strategy dependent on the RD1and other factors, the pathogen undoubtedly promotes bacterial cell-to-cell spread [25,26]. M. avium escapes macrophage killing by expressing MAV2054 virulence factor and promoting the intrinsic apoptotic pathway in cultured macrophages as well as in vivo via production of reactive oxygen species, damaging mitochondrial membrane [15]. Recent studies by our group have demonstrated that M. avium infection stimulates different modes of apoptotic escape in the primary-and secondary-infected cells [10,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophage apoptosis is an innate defense mechanism and is a strictly regulated process, M. avium escapes apoptotic killing [8,14]. It has been demonstrated that the pathogen targets intrinsic pathway to promote the apoptotic death in cultured macrophages and in vivo via production of reactive oxygen species, leading to mitochondrial membrane potential loss [15]. Moreover, M. avium uses apoptosis as one of mechanisms to spread from cell-to-cell and for dissemination [8,10].…”
Section: Introductionmentioning
confidence: 99%